Piezothermoelastic interaction in piezoelectric rods induced by a timed laser pulse without energy dissipation - Zuhur Alqahtani; Ibrahim Abbas; Alaa A. El-Bary (Case Studies in Thermal Engineering)
The main aim of this article is to study the piezo-thermoelastic interaction in piezoelectric rods without energy dissipation due to a laser heat source with a timed pulse. Laplace transforms are used to represent the analytical solutions in the transformations domain. The governing equations of piezo-thermoelasticity in the Green and Naghdi model (GNII model without energy dissipation) in the presence of a laser heat source with a timed pulse are solved exactly in the Laplace domain, calculating the temperature, the stress, the displacement, and the electric potential. Numerical Laplace inversion is then used to find the general solution of the variables under study, which are then graphically shown.